PENGARUH ENVIRONMENTAL PERFORMANCE DAN ENVIRONMENTAL DISCLOSURE TERHADAP ECONOMIC PERFORMANCE - Widarto, Danny; Mudjiyanti, Rina (Media Ekonomi, 2015)
The aim of this research was to examine the influences of the environmental performance andenvironmental disclosure to the economic performance. This research focused on the public companiescomplying with PROPER KLH RI in the period of 2010-2012. The sample was 35 companies. The datawere then analyzed using multiple linear regressions. Based on the analysis, it was proved that theenvironmental performance partially had significant effect to the economic performance. Meanwhile, theenvironmental disclosure partially had no significant effect to the economic effect. Yet, simultaneouslyboth environmental performance and environmental disclosure influenced significantly to the economicperformance, meaning the concept of environmental accounting begins to have Indonesian publicacceptance. The model of environmental accounting has improved and influenced the economicperformance.Keywords: environmental accounting, environmental performance, environmental disclosure, andeconomic performance.